(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2015)
A field experiment was conducted to observe the effect of inorganics, bio-fertilizers and FYM applied to rice-fallow sorghum on soil properties and biological activity at Agricultural College Farm, Bapatla during 2012. Soil samples were collected at flowering and harvest of the crop and were analysed for bulk density (BD), porosity, pH, electrical conductivity (EC), organic carbon, N, P, K and micronutrients by standard methods. Results indicated that the soil properties viz., bulk density, porosity, pH and EC were not markedly influenced by the imposed treatments, while significantly high organic carbon was recorded in FYM treated plots. There was a significant influence of the treatments on available nitrogen and phosphorus, but not on potassium. Among micronutrients (Cu, Zn, Mn and Fe), the treatmental influence was significantly related to Fe only. Addition of inorganics in combination with organics and bio-fertilizers proved to be more efficient in improving the microbial population and enzyme activities (urease and dehydrogenase) significantly. Int. J. Agril. Res. Innov. & Tech. 5 (1): 10-14, June, 2015